FOXP3 rs2294021 Polymorphism Towards the Susceptibility To Breast Carcinoma In North Indian Population - Mourya, Ajit (My University, 2013)
FOXP3, the main regulator of Treg (regulatory T) cells, is down-regulated in breast carcinoma and other cancers. The rs2294021 FOXP3 polymorphism contributes to FOXP3 down-regulation thereby weakens its tumor suppressing activity. The aim of our study was to evaluate the potential influence of FOXP3 polymorphism on breast cancer, we conducted a case-control study in north Indian women. FOXP3 genotyping was conducted in 33 breast carcinoma patients and 28 age-frequency matched cancer-free controls. Genotypes were determined by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method. Experiment data was analyzed using Hardy−Weinberg equilibrium. The C/C genotype was found to be significantly associated with increased risk of breast carcinoma occurrence (OR= 3.0, 95% C.I; 0.372–24.171, p-value=0.29184) compared with the T/T or T/C (OR=1.800, 95%CI; 0.278-11.635, p-value=0.53250) genotype .The increased risk for breast carcinoma related to heterozygous genotype was more pronounced in subjects over 40 years .Our findings suggest that rs2294021 FOXP3 polymorphism may be a potential contributor for development of breast carcinoma in north Indian women.
M.Sc. (Biotechnology)
Keywords: Brest cancer; FOX P3; Regulator T-Cell